Analisis Supervisi klinis terhadap Peningkatan Kompetensi Guru di SMPN 4 Karangploso - Zen Risky Noval; Alya Chandra Ariyanti; Dimas Muhammad Rasyid Maulidil Kiram; Shobihatul Fitroh Noviyanti (Al-Kindi, 2026)
This study aims to determine the implementation of clinical supervision and the application of the E-Kinerja system in improving teacher performance at SMP Satu Atap. This study used a descriptive qualitative method with data collection techniques in the form of interviews, observations, and documentation. The results showed that supervision was conducted once every semester through classroom learning observations carried out by senior teachers, principals, and supervisors according to their respective roles and positions. The implementation of supervision not only focused on assessment but also on guidance and improvement of the teaching and learning process. In addition, the implementation of the Platform Merdeka Mengajar (PMM) and E-Kinerja systems helped make the observation process more transparent, systematic, and integrated with Teacher Performance Targets (SKP). Teachers also conducted self-reflection and follow-up actions after the observation as an effort to continuously improve their competencies. Despite various challenges related to students’ social and academic conditions, the school continued striving to improve the quality of education through structured supervision implementation. Keywords: clinical supervision, E-Kinerja, learning observation, PMM, teacher performance